Hukuman Mati dan Hak untuk Hidup di Indonesia: Tinjauan HAM terhadap Undang-undang Nomor 1 Tahun 2023 - Ade Arga Wahyudi; Wami Irma Suryani; Zul Fahmi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the application of the death penalty in Indonesia from a human rights perspective, with a focus on legal reforms introduced through Law No. 1 of 2023 on the Criminal Code, and discusses whether the introduction of a 10-year probation period as an alternative to immediate execution can effectively protect the right to life while addressing ethical and justice dilemmas. This study uses a normative legal research method with a legislative approach. Primary legal materials were obtained from Law No. 1 of 2023, the Criminal Code, and other official legal documents, while secondary materials were obtained from credible legal and non-legal books and journals. Data collection was conducted through document study, and qualitative analysis was performed using a comparative and interpretative approach. The findings show that although the trial mechanism reflects progress in aligning criminal law with human rights values, there are still significant gaps, particularly regarding the risk of judicial error and unequal access to legal representation. These issues highlight the urgent need for harmonization of regulations with international human rights instruments, strengthening of institutional capacity among legal actors, and independent oversight mechanisms. This study concludes by recommending further interdisciplinary and empirical research to support more equitable and socially responsive criminal law reform that upholds the protection of human rights.